Earthworm‐Inspired Ultra‐Durable Sliding Triboelectric Nanogenerator with Bionic Self‐Replenishing Lubricating Property for Wind Energy Harvesting and Self‐Powered Intelligent Sports Monitoring - Mengjiao Liu; Xin Zhang; Yue Xin; Dongxu Guo; Guangkai Hu; Yifei Ma; Bin Yu; Tao Huang; Chengchang Ji; Meifang Zhu; Hao Yu (Advanced Science, 2024)
Abstract Triboelectric nanogenerators (TENGs), a promising strategy for harvesting distributed low‐quality power sources, face inevitable bottlenecks regarding long‐term abrasion and poor durability. Herein, both issues are addressed by selecting an earthworm‐inspired self‐replenishing bionic film (ERB) as the tribo‐material of sliding‐freestanding TENGs (SF‐TENGs), it consists of an interconnected 3D porous network structure capable of storing and releasing lubricant under cyclic mechanical stimuli. Thanks to the superiority of self‐replenishing property, there is no need for periodic replenishment and accurate content control of lubricant over the interfacial‐lubricating SF‐TENGs based on dense tribo‐layers. Additionally, an SF‐TENG based on ERB film (ERB‐TENG) demonstrates remarkable output stability with only a slight attenuation of 1% after continuous operation for 100 000 cycles. Moreover, the ERB‐TENG displays a distinguished anti‐wear property, exhibiting no distinct abrasion with an ultra‐low coefficient of friction (0.077) and maintaining output stability over a prolonged period of 35 days. Furthermore, integration with an energy management circuit enables the ERB‐TENG to achieve a 39‐fold boost in charging speed. This work proposes a creative approach to enhance the durability and extend the lifespan of TENG devices, which is also successfully applied to wind energy harvesting and intelligent sports monitoring.